Advances in the determination of forage and forestry production and greenhouse gas mitigation in silvopastoral systems in the Espinal Periestépico region of Argentina - Montenegro, Agustín Rodrigo; Teran, Ezequiel Jesús; Torres, Yanina Alejandra; Blazquez, Francisco Ruben; Juliarena, María Paula; Gyenge, Javier (Springer, 2024)
The objective of this study was to evaluate the herbaceous aboveground biomass production (DM kg ha−1), the woodland structure and greenhouse gas (GHG) emissions mitigation capacity of agroecosystems under silvopastoral use in the semi-arid region located at the southern part of the Argentinean Pampa region called Espinal Periestépico. Two contrasting vegetable covers (woody vs. herbaceous) were selected in three locations (Algarrobo, Villalonga, and Patagones) along a precipitation and vegetation gradient. We measured in each location/cover the biodiversity/size of woody species, soil water dynamics at different depths, and forage productivity, methane (CH4) concentration profiles and potential oxidation rates of CH4 in laboratory conditions at different soil layers. Tree density varied between 820 and 1088 individuals ha−1, a higher value compared to previous national forest inventory data. The average aboveground biomass of forage species in woody and herbaceous cover was greater than non-forage ones. A different soil water dynamics were observed according to vegetable cover and soil depth. Finally, CH4 oxidation rate revealed different patterns between locations and vegetable cover. The result highlight the importance of considering vegetation cover and water dynamics in the sustainable management of these systems, while recognizing their ecosystem services, especially their potential to mitigate greenhouse gas (GHG) emissions.